REVIEW PENELITIAN TERKAIT TATA KELOLA DAN AKUNTABILITAS KOPERASI DI INDONESIA - Widiyanto Widiyanto; Dwi Cahyo Utomo (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
The purpose of this study is to examine specifically related to the governance and accountability of cooperatives that have been carried out in Indonesia. This study used a qualitative design, with a population of 125 journals and through purposive sampling, a sample of 35 journals was obtained. The results of the journal review can be concluded: (1). The trend of research on governance and accountability of cooperatives in Indonesia is mostly done with a qualitative design, obtained the concept: to improve governance can be done through socialization and training on SPI to managers; comply with ethical principles and rules; the accountability aspect must be audited by KAP; the role of government; principles of transparency, accountability, responsibility, independence and fairness. Measurement of the dimensions of democracy, the quality of human resources, transparency, accountability, responsibility, independence and fairness. Good financial planning, transparency and accountability in financial management, increasing management commitment, knowledge, understanding of the duties and authorities of management regarding business risks and communication. Factors of members, administrators and supervisors as well as honesty and understanding; Sharia good corporate governance requires supervision from the Supervisory Board. Understanding of the important role of cooperatives for improving the community's economy, consistency in preparing financial reports. (2). Based on the quantitative design, it is concluded: cooperative governance and accountability have a positive and significant effect and accountability as a mediating variable on cooperative performance, there is no difference between financial accountability performance before and during the pandemic, cooperative reform has a positive and significant effect on cooperative governance and cooperative governance has no effect on the effectiveness of lending.